Interplay between lysosomal, mitochondrial and death receptor pathways during manganese-induced apoptosis in glial cells - Gorojod, Roxana Mayra (2017)
Manganese (Mn) is an essential trace metal which plays a critical role in brain physiology by acting as a cofactor for several enzymes. However, upon overexposure, Mn preferentially accumulates within the basal ganglia leading to the development of a Parkinsonism known as Manganism. Data from our group have proved that Mn induces oxidative stress-mediated apoptosis in astrocytoma C6 cells. In the present study we described how cathepsins impact on different steps of each apoptotic cascade. Evidence obtained demonstrated that Mn generates lysosomal membrane permeabilization (LMP) and cathepsin release. Both cathepsins B (Ca-074 Me) and D (Pepstatin A) inhibitors as well as Bafilomycin A1 prevented caspases-3, -7, -8 and -9 activation, FasL upregulation, Bid cleavage, Δφm disruption and cytochrome c release. Results from in vivo studies showed that intrastriatal Mn injection increased cathepsin D levels from corpus striatum and substantia nigra pars compacta. Our results point to LMP and lysosomal cathepsins as key mediators in the apoptotic process triggered by Mn. These findings highlight the relevance of targeting the lysosomal pathway for Manganism therapy.